Broad Money Demand and Financial Liberalization in Greece - Sharma, Sunil; Ericsson, Neil. (Washington, D.C. : International Monetary Fund, 1996)
This paper develops a constant, data-coherent, error correction model for broad money demand (M3) in Greece. The model contributes to a better understanding of the effects of monetary policy in Greece, and of the portfolio consequences of financial innovation in general. The broad monetary aggregate M3 was targeted until recently, and current Greek monetary policy still uses such aggregates as guidelines, yet analysis of this aggregate has been dormant for over a decade. Inspite of large fluctuations in the inflation rate, introduction of new financial instruments, and liberalization of the financial system, the estimated model is remarkably stable. The dynamics of money demand are important, with price and income elasticities being much smaller in the short run than in the long run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet